PRONOUNS IN AWANKARI DIALECT OF LAHNDI: A DESCRIPTIVE STUDY - Ameer Sultan; Shahid Hussain Mir; Shahid Abbas (PalArch's Journal of Archaeology of Egypt / Egyptology, 2023)
Awankari is a dialect of Lahndi spoken in Tehsils of Naushera (Soon Sakessar Valley), Talagang and Lawa in the province of Punjab and is the daughter language of Indo-Aryan languages family. It has more than 300,000 speakers in the region but a significant number of migrated speakers preserved the dialect in the districts of Sargodha, Multan, Bhakhar, Bahawalnagar and Bahwalpur. The forefathers of these immigrants left their homeland as a result of land allotment by British government and Pakistan Army. As Awankari" refers to a very localized or lesser-known dialect that has not been widely documented or recognized in available sources. The present study aims to describe and document the pronouns used in Awankari. The study used qualitative method to describe the pronouns. The study used convenience sampling technique to select the sample of the study and record the data. The study reveals that like other dialects of Lahndi and Punjabi Awankari pronouns are used both honorifically and non-honorifically to perform different grammatical functions. The study recommends a further syntactic investigation for more in-depth study of other grammatical features of Awankari.